368 Poor maternal nutrition during gestation alters whole body and cellular metabolism in offspring. (7th December 2018) - Govoni, K; Reed, S; Zinn, S
Abstract: Poor maternal nutrition during gestation can negatively impact both fetal and postnatal growth and metabolism of offspring. Specifically, both under- and over-feeding during gestation have been shown to reduce muscle development, increase adipogenesis, alter mesenchymal stem cell and satellite cell function, and create metabolic dysregulation in offspring. We and others demonstrated altered glucose metabolism, insulin sensitivity and leptin resistance; however, the mechanisms contributing to these systemic changes are not well established. These systemic effects are likely due to changes in multiple cellular systems of key metabolic tissues such as liver, muscle and adipose. Specifically, we have demonstrated that mitochondrial metabolism is altered in offspring mesenchymal stem cells and that muscle metabolites are altered in response to both under- and over-feeding of ewes during gestation. Through a comprehensive understanding of the effects of maternal programming through diet on the multiple systems involved in metabolism, we can identify improved methods to manage these offspring and increase efficiency of production.